Influence of nutritional management prior to adaptation to a feedlot diet on ruminal microbiota of Nellore cattle - Pinto, Ana Carolina Janssen [UNESP] (2023)
The objective of this study was to evaluate the effect of either a limited forage intake or concentrate supplementation prior to the adaptation to high-concentrate diets on dry matter intake, ruminal pH, bacteria, and protozoa of Nellore cattle. The experiment was designed as a two 3×3 Latin square, and six cannulated Nellore steers were used. Each experimental period was composed by three feeding phases: pre-adaptation (14 days), adaptation (12 days), and finishing (seven days) diet, in a total of 33 days per period. The steers were assigned to one of three pre-adaptation dietary treatments: control (Tifton hay fed ad libitum + mineral supplement), restriction (Tifton hay fed at 1.4% of BW + mineral supplement), and concentrate (Tifton hay fed ad libitum + 0.5% of BW of a mix of concentrate feedstuffs and mineral supplement). The adaptation period consisted of two adaptation diets, which contained 72 and 79% concentrate for six days each. The finishing diet contained 86% concentrate. During the pre-adaptation phase, restricted cattle had higher pH than concentrate-fed cattle. There was a reduction in M. elsdenii relative population in cattle from either restriction or concentrate groups. During adaptation and finishing phases, cattle from concentrate group had smaller F. succinogenes populations compared with the control group. The previous nutritional backgrounds impact ruminal microbiota during adaptation and finishing phases without causing any negative effect on ruminal pH. Feeding concentrate prior to the adaptation positively impacted the transition to high-concentrate diets and promoted increased dry matter intake.